Development And Analysis Of Linear Resonant Scanner With Torsional Mechanism - Koay, Loke Kean (2013)
Large size mirror scanners are needed in several scanning technologies such as, ultra short-throw projector, free-space optical communications and barcode scanner. Several researches on large size mirror in microelectromechanical systems (MEMS) scanner were conducted. For instance, research on micromachined polysilicon microscanners has been performed for barcode scanner. However, the curvature of the microscanners causes image distortion. Furthermore, high operation voltages of the MEMS scanner deter the usage of MEMS scanner in hand-held applications. In this research, a linear resonant scanner consisting of an electronically driven mechanically-resonant torsional spring-mirror system was developed for display applications. The scanner was designed according to the functional components such as compliant structure and actuator. The torsional spring which is the compliant structure was modeled with finite element analysis (FEA) and geometry studies were conducted. The optimized torsional spring with the lowest stress level was selected for the design. The actuator of air core coil (ACC) was used in the scanner; geometry study was used to maximize the magnetic forces of the ACC. The ACC of with minimum length, minimum inner radius and maximum outer radius was used. Besides, experimental analysis and FEA of the scanner showed that resonant frequency, angular displacement and stress level are affected by the magnet position on the suspended plate. After the scanner design, several characteristic studies were conducted. A nonlinear damping model is proven to be able to analyze and predict the free vibration response of the scanner based on experimental results.